WEWENANG KEPALA DAERAH DALAM PENGELOLAAN BADAN USAHA MILIK DAERAH - Ryan Surya Pradhana (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2019)
Law Number 23 of 2014 concerning Regional Government divides Regional-Owned Enterprises into Regional Public Companies and Regional Companies. The Regional Government Law divides government affairs into three classifications, namely absolute government affairs, concurrent government affairs, and general government affairs. Furthermore, government authority is the right and obligation of the government in carrying out government actions or actions as regulated in Article 1 point 6 jo. Article 17 through Article 19 jo. Article 1 point 8 of the Government Administration Law. Regional government authority is the implementation of government affairs as regulated in Article 1 point 5 of the Regional Government Law, which states that government affairs are governmental powers which are the authority of the President whose implementation is carried out by state ministries and administrators of Regional Governments to protect, serve, empower and prosper the community, among others through the establishment of Regional owned enterprises. Regional-owned enterprises are established through regional regulations based on regional needs and business field feasibility. Regional needs are assessed through studies covering aspects of public services and community needs. Meanwhile, the feasibility of the business sector of Regional Owned Enterprises is studied through analysis of economic feasibility, market and marketing analysis, financial feasibility analysis, and analysis of other aspects. Analysis of other aspects contains aspects of laws and regulations, availability of technology, and availability of human resources.